Structural and Optical Characteristics of Silica Nanotubes Using CNTs as Template - Malekfar, Rasoul; Rajabi, M. Hassan; Ara, M. Hossein Majless (Nano-Micro Letters, 2010)
Silica coated multi-wall carbon nanotubes (MWCNTs), silica@MWCNTs and nanocomposites were synthesized by a sol-gel method. By using the synthesized nanocomposites and also CNTs as templates, silica nanotubes (silica-NTs) were prepared. The optical properties of fabricated nanocomposites and nanotubes were characterized by back-scattering micro Raman, UV/Vis/NIR and FT-IR spectra, which show the presence of CNTs structure in the nanocomposites. UV/Vis/NIR and FT-IR spectra also show the presence of silica compounds. The recorded spectra from UV/Vis/NIR and FT-IR also confirm the presence of silica compounds in the nanotubes. The results of FE-SEM imaging data indicate that the synthesized samples are MWCNTs coated uniformly by silica molecules, which act as the template to synthesize silica-NTs.